Alpha beta but not gamma delta T cell clones in synovial fluids of patients with reactive arthritis show active transcription of tumour necrosis factor α and interferon γ - Rihl, M (2004)
Methods: Complementary DNA based microarrays containing the specific sequence of 56 cytokine transcripts were used for screening. Selected genes were confirmed by reverse transcriptase-polymerase chain reaction assay. Results: Microarray showed that transcripts encoding for interferon γ and tumour necrosis factor α were expressed by all CD8+ and CD4+ T cell clones. However, γδ+ T cells predominantly expressed transforming growth factor ß2 and granulocyte monocyte-colony stimulating factor. Conclusion: T lymphocyte clones from the joint of patients with ReA exhibit differential cytokine expression profiles. CD8+ and CD4+ T cells demonstrate a Th1 mediated profile, whereas γδ+ T cells show a more heterogeneous and less proinflammatory Th3 driven pattern.